ANALYSIS OF THE QUALITY OF ISAE 3000 ASSURANCE STATEMENTS ON CORPORATE SUSTAINABILITY REPORTS ACROSS STOCK EXCHANGES IN SEVERAL COUNTRIES: A 2020-2022 STUDY - Gavriel Faith Nangoy,; Carmel Meiden,; Suheriyatmono, (International Journal of Social Science, 2024)
While sustainability reporting has made significant strides in recent years, a noticeable gap persists between reporting practices and corresponding assurance measures. This paper emphasizes the alignment of sustainability assurance statements with the essential elements mandated by the ISAE 3000 assurance standard. A content analysis was conducted on the assurance statements of twenty (20) publicly listed companies across 20 different exchanges over a three-year span from 2020 to 2022. The analysis employed a quantitative approach, utilizing scoring to assess the alignment of the content with the requirements of the assurance standard. The research instrument was based on the minimal content elements of ISAE 3000 and developed by previous studies. The study reveals high quality levels among all assurance providers in the sample. Country-wise, the quality level is high for all countries except Japan, Thailand, Denmark, and Australia, which exhibit a medium quality level. Similarly, sectors in the sample generally exhibit a high quality level, except for consumer goods and industrial sectors, which demonstrate a medium quality level. The study also identifies variability in the content elements of assurance statements.